PENGEMBANGAN PENUNTUN PRAKTIKUM YANG DILENGKAPI GAMBAR PADA FUNGI (JAMUR) UNTUK SEKOLAH MENENGAH ATAS (SMA) - Roza, Diana; Helendra, Helendra; Maizeli, Annika (Pendidikan Biologi, 2013)
ABSTRACT        Learning process was the core of formal education through which the teacher, learning materials and students interacted. The first was considered as the one who played the main role especially. One of the materials which required the students to do practice was fungus topics. Related to this, teacher developed learning material which was accompanied with representative and contextual pictures in order to help the students do practicum. This research was aimed at producing a manual which was valid and practical for teaching fungus topics to the Senior High School students. This was an experimental research which referred to 4-D model. The result of theresearch  indicated that the manual which was accompanied with pictures produced was valid and very practical.